2017
DOI: 10.1111/evo.13197
|View full text |Cite
|
Sign up to set email alerts
|

Independent cytoplasmic incompatibility induced byCardiniumandWolbachiamaintains endosymbiont coinfections in haplodiploid thrips populations

Abstract: Cardinium and Wolbachia are common maternally inherited reproductive parasites that can coinfect arthropods, yet interactions between both bacterial endosymbionts are rarely studied. For the first time, we report their independent expression of complete cytoplasmic incompatibility (CI) in a coinfected host, and CI in a species of the haplodiploid insect order Thysanoptera. In Pezothrips kellyanus, Cardinium-induced CI resulted in a combination of male development (MD) and embryonic female mortality (FM) of fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 63 publications
(151 reference statements)
2
67
0
2
Order By: Relevance
“…Each cross combination contained at least 24 biological repeats. Following previous studies (Mouton et al, 2005;Nguyen et al, 2017), samples that produced fewer than 10 eggs were excluded.…”
Section: Fecundity Assaymentioning
confidence: 99%
“…Each cross combination contained at least 24 biological repeats. Following previous studies (Mouton et al, 2005;Nguyen et al, 2017), samples that produced fewer than 10 eggs were excluded.…”
Section: Fecundity Assaymentioning
confidence: 99%
“…Haplo‐diploid thrips populations co‐infected by Wolbachia and Cardinium induce complete CI. Whereas Wolbachia density in these thrips co‐infections is higher than Cardinium density, Wolbachia removal does not impact Cardinium density, suggesting a lack of competition within hosts (Nguyen et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Symbiont co-infections are common in arthropods, such as spider mites, aphids and grasshoppers (Machtelinckx et al, 2012;Lukasik et al, 2013;Wamwiri et al, 2013;Funkhouser-Jones et al, 2015;Moutailler et al, 2016;Zhang et al, 2016;Zytynska and Weisser, 2016;Nguyen et al, 2017). The presence of co-infections in mites and other arthropods raises questions about how such infections are generally maintained.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Nguyen et al (2017) found the first-recorded CI in Thysanoptera, caused by Wolbachia and Cardinium coinfections in Pezothrips kellyanus. In haplodiploid organisms, CI can cause female mortality (FM) or a male development (MD) phenotype (Vavre et al 2001, Nguyen et al 2017.…”
Section: • Effect Of Symbionts On Host Sex Ratio -Bacterial Endosymbimentioning
confidence: 99%
“…Recently, Nguyen et al (2017) found the first-recorded CI in Thysanoptera, caused by Wolbachia and Cardinium coinfections in Pezothrips kellyanus. In haplodiploid organisms, CI can cause female mortality (FM) or a male development (MD) phenotype (Vavre et al 2001, Nguyen et al 2017. In FM, all fertilized eggs in a CI cross fail to develop, while in MD, fertilized eggs survive but as haploid males (Vavre et al 2001, Nguyen et al 2017.…”
Section: • Effect Of Symbionts On Host Sex Ratio -Bacterial Endosymbimentioning
confidence: 99%